1981
DOI: 10.1093/infdis/144.1.33
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Serologic, Histologic, and Immunohistologic Findings in the Prognosis of 88 Asymptomatic Carriers of Hepatitis B Surface Antigen

Abstract: Eighty-eight asymptomatic carriers of hepatitis B surface antigen (HBsAg) were followed with biochemical, serologic, histologic, and immunohistologic studies over a period of four years. None of the 78 HBsAg carriers with normal or minimally changed liver tissue, antibody to hepatitis B e antigen (HBeAg) in serum, and no intranuclear hepatitis B core antigen (HBcAg) developed a chronic inflammatory liver disease. Four individuals lost circulatory HBsAg, and at least two individuals terminated their HBsAg carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Several histologic follow-up studies have also been performed in Taiwan (32)(33)(34) and other areas (35)(36)(37), but there have been few histologic studies in children (8)(9)(10)(11). Several studies on adult asymptomatic HBsAg carriers have shown that histologic lesions in the liver are frequently absent or minor (nonspecific); CPH is occasionally diagnosed, while CAH or cirrhosis is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Several histologic follow-up studies have also been performed in Taiwan (32)(33)(34) and other areas (35)(36)(37), but there have been few histologic studies in children (8)(9)(10)(11). Several studies on adult asymptomatic HBsAg carriers have shown that histologic lesions in the liver are frequently absent or minor (nonspecific); CPH is occasionally diagnosed, while CAH or cirrhosis is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Its incidence has been estimated to be 0.4% to 2% per year in Western countries, [1][2][3] where HBV infection usually occurs in adults. [1][2][3][4][5][6][7][8][9] In Taiwan, an endemic area of HBV infection that usually occurs perinatally or during early childhood, 10,11 the annual incidence was comparably low, ranging from 0.1% to 0.8%. 12,13 Although several investigators reported a good prognosis for such patients, 1,3,6,14 some reports suggested that cirrhosis may still develop in spite of HBsAg clearance, and some other patients may even progress to hepatocellular carcinoma (HCC).…”
mentioning
confidence: 99%
“…Thus The clearance of HBsAg from serum of patients with acute hepatitis B usualIy indicates recovery from infection (1, 2). However, the clinical significance of the disappearance of HBsAg during the course of chronic hepatitis B has not been fully explained because the clearance ratio seems to be very low (3)(4)(5)(6). Although several investigators reported a good prognosis for such patients (3-51, some patients had liver diseases (4,6) and related complications develop.…”
mentioning
confidence: 99%